Leadership Reinvented how to foster empathy, servitude, diversity, and innovation in the workplace - Khan, Hamza (Rockridge, 2021)
Traditional leadership has been long overdue for reinvention. Become a respected and successful leader in the modern workplace with Leadership, Reinvented. You?ll find actionable insights, practical advice, and essential strategies for people in various organizations and levels of leadership.
Includes index
Keywords: Leadership